Association between maternal prepregnancy diabetes mellitus and preconception folic acid supplement use by Hispanic ethnicity: Findings from Georgia, New York City, and Puerto Rico PRAMS 2016–2018. Issue 15 (12th August 2022) - Guzman, Iridian A.; Kramer, Michael R.; Kancherla, Vijaya
Abstract: Background: Maternal ethnicity, prepregnancy diabetes, and preconception folic acid intake, are all associated with increased risk of neural tube defects in the United States. We assessed the association between prepregnancy diabetes and preconception folic acid use by Hispanic ethnicity. Methods: We used population‐based, cross‐sectional survey data from New York City, Georgia and Puerto Rico's 2016–2018 Pregnancy Risk Assessment Monitoring System (PRAMS). Prepregnancy Type 1 or Type 2 diabetes was self‐reported. Adequate preconception folic acid intake was defined as intake of a multivitamin, a prenatal vitamin, or a folic acid vitamin 4–7 times/week during the month before pregnancy. Multivariable logistic regression was used to calculate adjusted prevalence odds ratio (aPORs) and 95% confidence intervals (CI), stratified by Hispanic ethnicity. Results: Prepregnancy diabetes was reported by 2.9% of Hispanic and 3.6% of non‐Hispanic participants. Adequate preconception folic acid use was reported by 25.9% and 39.9% of Hispanics and non‐Hispanics, respectively. There was an inverse association between prepregnancy diabetes and preconception folic acid use among Hispanics (aPOR = 0.75; 95% CI = 0.31, 1.81), while the association was positive among non‐Hispanics (aPOR = 1.26; 95% CI = 0.70, 2.26); however, the 95% confidence intervals for both groups contained the null value. Conclusions: The association between prepregnancy diabetes and folic acid intake varied by Hispanic ethnicity. Our hypothesis that reproductive‐aged women with prepregnancy diabetes may receive timely diabetic care, including health counseling to take preconception folic acid, was not supported by our study data. Future studies should examine the association in additional PRAMS sites. Preconception health screening, and folic acid intake among Hispanics, should be strengthened.